Russian Federation : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that real GDP growth in Russia has slowed, amid weak investment and external demand. Yet, the economy remains close to full capacity, with unemployment at historic lows and capacity utilization at pre-crisis highs. Short-term indicators are mixed, but on balance suggest some recovery of activity in recent months, indicating a stronger growth outlook for the second half of 2013. The near-term outlook is for moderate growth and inflation at the upper end of the target range of the Central Bank of the Russian Federation (CBR).